Circular Approach in Green Planning Towards Sustainable Cities. - Lavagna, Monica (Springer, 2020)
Cities are like organisms, drawing in resources and emitting wastes. In nature, organisms are related to ecosystems characterized by a circular metabolism, so a green planning to move towards sustainable cities needs to adopt a circular approach to the way in which are managed the resources consumed (materials, food, energy, water and land) and the emissions produced (solid waste, airborne and waterborne) in cities and their related territories. Initially, the origins of the theme of circularity are illustrated, in particular, in relation to urban applications (urban metabolism) and territorial (industrial ecology) and current developments, with the analysis of a virtuous example. Thereafter, some possible strategic approaches to favour urban circularity (urban mining, building regeneration) are analysed, highlighting the importance of flow mapping and the creation of exchange platforms. Finally, some methods of assessing environmental impacts are shown to verify the effectiveness of circularity with respect to the objective of sustainability, and examples of benchmarks/targets adopted in some concrete cases experienced are presented.
Keywords: Stadtbegrünung; Nachhaltige Stadtentwicklung; Stoffkreislauf; Metabolismus; Urban Mining; Kreislaufwirtschaft; Ressourcenmanagement; Gebäudeerhaltung; Umweltbilanz; Ökologischer Stadtumbau; Umweltwirkung